Perawatan endodontik konvensional pada gigi molar pertama kanan rahang bawah dengan kista radikuler Conventional endodontic treatment in lower right first molar with radicular cyst - Badi Soerachman; Moch. Richata Fadil; Endang Sukartini; Milly Armilia (Journal of Dentomaxillofacial Science, 2012)
Abnormalities of the teeth that have had periapical endodontic treatment generally due to recurrent infections of root canal. Infection of the root canal is caused by leakage due to poor quality of coronal restoration and iatrogenicfactors. Root canal treatment of the tooth with periapical cyst generally do conventionally. Medication materialsused for healing of periapical lesions is calcium hydroxide, since it has properties not irritating, alkaline pH andantibacterial capabilities, so it is a biological stimulator for the formation of hard tissue in the area of damage andis expected to accelerate the healing process. It was reported the case of a 23-year-old student came to the Dentalclinic of Conservation Specialist RSGM Sekeloa with complaints lower right back teeth has restored with amalgam,no pain, but less comfortable when chewing. The results obtained after treatment with calcium hydroxide andmedikamen gutta percha filling with resin-based root canal cement. Approximately 4 months later, the periapicalradiolucent area had thinned. So it was concluded that conventional endodontic treatment proved to heal periapicallesions including cysts, as long as the treatment is taken adequately.